Temperature and relative humidity dependency of film formation of polymeric latex dispersions - Chen, Xuelian (Langmuir : the ACS journal of surfaces and colloids, 2011)
Thermogravimetric analysis and a synchrotron small-angle X-ray scattering technique were employed to characterize the structural evolution of a polymeric latex dispersion during the first three stages of film formation at different temperatures and relative humidities. Three intermediate stages were identified: (1) stage I*, (2) stage I**, and (3) stage II*. Stage I* is intermediate to the conventionally defined stages I and II, where latex particles began to crystallization. The change of drying temperature affects the location of the onset of ordering, whereas relative humidity does not. Stage I** is where the latex particles with their diffuse shell of counterions in the fcc structure are in contact with each other. The overlapping of these layers results in an acceleration of the lattice shrinkage due to a decrease of effective charges. Stage II* is where the latex particles, dried well above their T(g), are deformed and packed only partially during film formation due to incomplete evaporation of water in the latex film. This is because of a rapid deformation of the soft latex particles at the liquid/air interface so that a certain amount of water is unable to evaporate from the latex film effectively. For a latex dispersion dried at a temperature close to its minimum film formation temperature, the transition between stages II and III can be continuous because the latex particles deform at a much slower rate, providing sufficient surface area for water evaporation